2019
DOI: 10.1038/s41598-019-56682-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of miRNAs as new tool for cutaneous vitality lesions demonstration in ligature marks in deaths by hanging

Abstract: This study aims to demonstrate that the application of miRNA expression in forensic pathology, in cases of hanging, applying the method on skin samples. The proposed investigative protocol allowed us to highlight a different miRNA expression in the skin ligature marks of subjects who died by hanging compared to healthy skin control samples. The results obtained showed an increase in the expression of miRNAs recognized as regulators of the inflammatory response in skin lesions such as miR125a-5p and miR125b-5p.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…In all cases of hanging, skin sections were removed at the neck in long strips perpendicular to the base of the ligature marks at the site of the major depth of the marks. In control cases skin samples were taken from the anterior face of the neck [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…In all cases of hanging, skin sections were removed at the neck in long strips perpendicular to the base of the ligature marks at the site of the major depth of the marks. In control cases skin samples were taken from the anterior face of the neck [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The tryptase level can be increased by cell autolysis or liquefaction [ 54 ]. Higher values of tryptase serum have also been found in other types of death, such as sudden infant death syndrome (SIDS), amniotic fluid embolism, and heroin-related deaths [ 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. β-tryptase is a more reliable indicator of acute mast cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, very few studies analyzed miRNA differences between ante and post-mortem skin lesions [ 77 , 78 ].…”
Section: Mirnas and Wound Vitalitymentioning
confidence: 99%
“…In another recent study, Neri et al investigated miRNA expression changes in the skin ligature marks of subjects who died by hanging. The authors found increased levels of miR125a-5p and miR125b-5p, two miRNAs involved in the inflammatory phase of wound healing, and also increased levels of miR92a-3p, miR128-3p, miR130a-3p (miRNAs with an anti-inflammatory role) compared to control skin samples [ 78 ].…”
Section: Mirnas and Wound Vitalitymentioning
confidence: 99%